2017
DOI: 10.1177/0886260517733281
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Between Observer Sex and Sexual Identity on Attributions of Blame With a Heterosexual Female Victim

Abstract: This article examines the difference in blame attribution between men and women, heterosexuals and homosexuals, and heterosexual males, heterosexual females, gay males, and lesbians in response to a vignette depicting the acquaintance rape of a heterosexual female ( n = 177). While the levels of empathy for the victim and blaming of the perpetrator were high for every group and blaming of the victim and rape myth acceptance were low for every group, some important trends emerged. Consistent with previous resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 81 publications
2
5
0
Order By: Relevance
“…We found that a one-unit increase in agreement that the scenario was rape translated to a 6.5-point value reduction in RMA. We also found that the respondent’s sexuality was a significant factor, where heterosexual respondents accepted rape myths at a lower rate than nonheterosexual respondents by 5.92 points, which is consistent with earlier findings (Diamond-Welch et al, 2021, discussed in independent variables).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…We found that a one-unit increase in agreement that the scenario was rape translated to a 6.5-point value reduction in RMA. We also found that the respondent’s sexuality was a significant factor, where heterosexual respondents accepted rape myths at a lower rate than nonheterosexual respondents by 5.92 points, which is consistent with earlier findings (Diamond-Welch et al, 2021, discussed in independent variables).…”
Section: Resultssupporting
confidence: 92%
“…In the first wave, there were four HITs—one for heterosexual men, one for heterosexual women, one for gay men, and one for lesbian women. We did not collect data from other sexualities and our sample was restricted to cisgender individuals (see Diamond-Welch, Mann, Bass, & Tollini, 2021). In the second wave, there were two HITs—one for transgender men another for transgender women.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations